-42=-3h

Simple and best practice solution for -42=-3h equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -42=-3h equation:


Simplifying
-42 = -3h

Solving
-42 = -3h

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '3h' to each side of the equation.
-42 + 3h = -3h + 3h

Combine like terms: -3h + 3h = 0
-42 + 3h = 0

Add '42' to each side of the equation.
-42 + 42 + 3h = 0 + 42

Combine like terms: -42 + 42 = 0
0 + 3h = 0 + 42
3h = 0 + 42

Combine like terms: 0 + 42 = 42
3h = 42

Divide each side by '3'.
h = 14

Simplifying
h = 14

See similar equations:

| -5n+18+21n-9= | | 13.4-x=8.1 | | 5v+-42=73 | | 7(y+5)+y=3(y+4)+7 | | -4+9y=9 | | 85=2t-37 | | 1=3u+7 | | -4(3-8n)=148 | | 2(-9x^2-3x+2)= | | X-4+3x+36=180 | | 30b^2+b-20=0 | | 2y-80=-3y-18 | | -9x^2+9x+1=0 | | 3.25z-(-.33+1.25z)=5.33 | | 6t^2-55t=-9 | | 2(x-1)+6y=-10 | | f(-3)=5x^3-2x^2-7x+2 | | 16x*(-2)=144 | | 2/5x.12= | | f(x)=5x^3-2x^2-7x+2f(-3) | | 10(1.6)-7y=-18 | | 3.25x-(.33+1.25x)=5.33 | | -0.2-2.6v=8.38 | | 2d^2+48d+46=0 | | x^2+3x+12=90 | | c-17=3.4 | | 3.4y-8=12 | | -2y-(-4y)= | | 8x+2(8.5)=30 | | 16=x-x-x+3+4+2 | | 3x=5x+6(2-x) | | 125x=17.50x+3.50 |

Equations solver categories